2007
DOI: 10.1016/j.exger.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase induction in T cells: A cure for aging and disease?

Abstract: Cells of the immune system are unique among normal somatic cells in that they have the capacity to upregulate the telomere-extending enzyme, telomerase, albeit in a precisely controlled fashion. Kinetic analysis of telomerase activity in long-term T cell cultures has documented that the high level of telomerase induced in concert with activation reaches a peak at 3-5 days, then declines by 3 weeks. The process is recapitulated during secondary antigenic stimulation, but by the third, and all subsequent stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 36 publications
1
64
0
1
Order By: Relevance
“…If in depression, shortened telomeres and heightened risk for medical illness bear causal relationships with each other, then telomere shortening could provide a 'missing link' to explain the higher-than-expected medical morbidity seen in depression (Musselman 1998;Brown 2004). Also, to the extent that telomere pathology is important in the pathophysiology of various illnesses, discovering the biochemical mediators leading to telomere shortening could lead to new classes of medications (Effros 2007). It is still not known if depression leads to accelerated 'aging' of mitotic cells.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…If in depression, shortened telomeres and heightened risk for medical illness bear causal relationships with each other, then telomere shortening could provide a 'missing link' to explain the higher-than-expected medical morbidity seen in depression (Musselman 1998;Brown 2004). Also, to the extent that telomere pathology is important in the pathophysiology of various illnesses, discovering the biochemical mediators leading to telomere shortening could lead to new classes of medications (Effros 2007). It is still not known if depression leads to accelerated 'aging' of mitotic cells.…”
Section: Editorialmentioning
confidence: 99%
“…If PBMC telomere dynamics directly mirror CNS ones (especially in mitotic cells such as hippocampal stem cells), this could help us understand cell-level pathology in the brain in depressed patients. Even if PBMC telomere length bears no relationship to hippocampal cell telomere length, shortened PBMC telomeres could still be significant in depression: (1) if shortened telomeres in peripheral immune cells eventuate in premature aging of those cells, this could result in impaired immune responsiveness and in hypersecretion of pro-inflammatory cytokines (Effros 2007;Leonard 2000); (2) as noted above, shortened telomeres have been associated with a variety of human medical illnesses, such as cardiovascular disease (Cawthon et al 2003) and dementia (von Zglinicki et al 2000;Franco et al 2006;Honig et al 2006;Martin-Ruiz et al 2006). If in depression, shortened telomeres and heightened risk for medical illness bear causal relationships with each other, then telomere shortening could provide a 'missing link' to explain the higher-than-expected medical morbidity seen in depression (Musselman 1998;Brown 2004).…”
Section: Editorialmentioning
confidence: 99%
“…When telomere lengths are measured in somatic cell cultures, a correlation is observed between telomere length and the number of cell divisions preceding senescence and death (Allsopp et al 1992). However, there is now a consensus that telomere length correlates to but does not cause aging in most individuals, with immunosenescence being the most tangible correlate (Effros 2007). Exceptions may be a variety of rare premature aging syndromes, such as dyskeratosis congenita (Kirwan and Dokal 2008) and idiopathic pulmonary fibrosis (Blasco 2005), and some cases of liver cirrhosis (Wiemann et al 2002) and myelodysplastic syndromes (Ohyashiki et al 1994), where mutations in telomere maintenance genes have been identified.…”
Section: What Is Not In the Model?mentioning
confidence: 99%
“…The immunological history of humans cannot, therefore, be mimicked in laboratory animals, which are subject to minimal exposure to such antigens [126]. Due to the extraordinarily low frequency of T cells specific for any single antigen, immune responses require a massive degree of proliferation in order to adequately control infection.…”
Section: Telomere Shortening Telomerase Enhancers and Immune Systemmentioning
confidence: 99%
“…Telomerase activation should prevent this telomere shortening and allow the body's immune system to fight a chronic infection indefinitely. Telomerase activation is a potential treatment for AIDS [126]. Although improved immunity cannot be considered a "cure" for aging and disease, the beneficial effects promise to enhance health and quality of life of the elderly and of persons infected with HIV-1, a disease characterized by accelerated aging of the immune system.…”
Section: Telomere Shortening Telomerase Enhancers and Immune Systemmentioning
confidence: 99%